Tasmannia lanceolata (Poir.) A.C.Sm. Pepperberry Extracts Inhibit the Growth of Selected Bacterial Gastrointestinal Pathogens - Winnett, Veronica; Cock, Ian Edwin (Pharmacognosy Communications)
Background: Tasmannia lanceolata (Poir.) A.C.Sm. Pepperberries contain high antioxidant contents and were used by the first Australians for a variety of therapeutic purposes. However, their growth inhibitory activity has yet to be verified against many bacteria. This study aimed to investigate the efficacy of T. lanceolata pepperberry extracts against diarrhoea- and dysentery-causing pathogens, as well as against non-pathogenic gastrointestinal bacterial strains. Materials and Methods: Powdered T. lanceolata pepperberries were extracted with solvents of varying polarity and screened for inhibition of bacterial growth against a panel of gastrointestinal bacteria. Susceptibility was assessed by disc diffusion techniques, whilst the minimum inhibitory concentrations (MICs) were quantified by liquid dilution assays. Extract toxicities was examined using Artemia nauplii bioassays and therapeutic indexes (TIs) were calculated as a measure of therapeutic safety. Results: Tasmannia lanceolata pepperberry extracts did not significantly inhibit the growth of the non-pathogenic/beneficial gut microflora bacteria A. faecalis or E. cloacae, but displayed noteworthy growth inhibitory activity against pathogenic A. hydrophila, E. coli, S. sonneii, C. freundii, P. fluorescens, S. newport, S. marcescens and B. cereus. The ethyl acetate extract was a particularly good inhibitor of bacterial growth, with MIC values as low as 375 μg/mL against some bacterial pathogens. All T. lanceolata pepperberry extracts were nontoxic in the Artemia nauplii assay, indicating their potential for clinical usage. Conclusion: The noteworthy inhibitory activity of the T. lanceolata pepperberry ethyl acetate extract reported herein indicates that it may be useful in treating bacterial gastrointestinal diseases and further studies are warranted. Furthermore, the T. lanceolata pepperberry ethyl acetate extract is nontoxic and does not adversely affect the growth of several bacteria components of the normal human gastrointestinal microbiome, further supporting its clinical use.
Keywords: Winteraceae; Mountain pepperberry; Tasmanian pepper; Disc diffusion; Liquid dilution assays; Food poisoning; Diarrhea.